(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Abscesses of the liver in subsequent years became somewhat rare as a result of the active use in medicine of antibiotics with a wide range of effects. Today, the factors contributing to this disease are: intensive chemotherapy, complications of diabetes mellitus, organ transplantation and decreased immunity due to AIDS. This article will give you the skills and knowledge of liver abscesses formation, treatment measures.